Design UI/UX Reservation Application Onengan Resort with Design Thinking Method Using Figma - Wibowo, Dimas Adi; Kristianto, Budhi (STMIK Banjarbaru, 2024)
The importance of designing UI and UX according to user needs in application development cannot be ignored. The Onengan Resort Reservation Application was conceptualized to make it easier for customers to make hotel reservations online, especially for those who live outside the city. In its development, a Design Thinking approach was used which prioritizes empathy towards users to create innovative and practical solutions. This process involves comprehensive idea generation as well as rigorous testing to ensure the effectiveness of the proposed solution. The UI/UX design of the Onengan Resort Reservation Application succeeded in achieving this goal by being attractive and user-friendly. This application prototype was assessed using Maze with a score of 84%, while the results of user trial analysis showed a Usability Testing score of 84.1%. This success confirms that the Design Thinking approach has been effective in producing an optimal user experience, ensuring that this application not only meets user needs but also provides convenience and satisfaction in its use.Keywords: User Interface; User Experience; Design Thinking Method; FigmaÂ AbstrakPentingnya mendesain UI dan UX sesuai kebutuhan pengguna dalam pengembangan aplikasi tidak bisa diabaikan. Aplikasi Reservasi Onengan Resort dikonsep untuk memudahkan pelanggan melakukan reservasi hotel secara online, terutama untuk mereka yang tinggal di luar kota. Dalam pengembangannya, digunakan pendekatan Design Thinking yang mengutamakan empati terhadap pengguna untuk menciptakan solusi inovatif dan praktis. Proses ini melibatkan generasi ide yang komprehensif serta pengujian yang teliti untuk memastikan keefektifan solusi yang diusung. Desain UI/UX Aplikasi Reservasi Onengan Resort berhasil mencapai tujuan tersebut dengan menarik dan ramah pengguna. Prototipe aplikasi ini dinilai menggunakan Maze dengan skor 84%, sedangkan hasil dari analisis uji coba pengguna menunjukkan skor Usability Testing sebesar 84,1%. Keberhasilan ini menegaskan bahwa pendekatan Design Thinking telah efektif dalam menghasilkan pengalaman pengguna yang optimal, memastikan bahwa aplikasi ini tidak hanya memenuhi kebutuhan pengguna namun juga memberikan kemudahan serta kepuasan dalam penggunaannya.Â